Intravitreal bevacizumab (Avastin) for choroidal neovascularisation secondary to pathological myopia: 6-month results. Issue 8 (24th July 2008) - Arias, L; Planas, N; Prades, S; Caminal, J M; Rubio, M; Pujol, O; Roca, G
Abstract : Background: To determine the efficacy and safety of intravitreal Avastin (bevacizumab) in the treatment of choroidal neovascularisation (CNV) secondary to pathological myopia (PM). Methods: This paper reports on a consecutive prospective study of patients with CNV secondary to PM who were treated with intravitreal bevacizumab (1.25 mg/0.05 ml). Patients underwent complete ophthalmic evaluation, which included best-corrected visual acuity testing measured with Early Treatment Diabetic Retinopathy Study charts, optical coherence tomography (OCT), and fluorescein angiography. Results: There were 17 eyes of 17 patients, and the mean age was 55.4 (SD 10.0) years. At the 6-month follow-up, the mean visual acuity improved by 8.4 letters (p = 0.04). Forty-one per cent of patients increased at least one line, and 17% increased more than six lines. There were no cases of moderate vision loss (⩾3 lines) or severe vision loss (⩾6 lines). The mean OCT foveal thickness decreased by 79.6 μm (p = 0.002). Favourable outcomes were obtained in all subgroups. Patients received an average of one injection. As a complication, there was a tear of the retinal pigment epithelium. No other ocular or systemic side effects were observed. Conclusion: In our study, intravitreal bevacizumab appeared to be safe and efficacious in eyes with CNV secondary to PM.